Analisis Pentingnya Pengelolaan Peserta Didik untuk Meningkatkan Mutu Pendidikan di Sekolah - Salsabil, Alfi Mardiyyah; Muthmainah, Annisa; Aulia, Naifa Fae; Syifa, Nazwa Al; Noviyanti, Salwa; Prihantini, Prihantini (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the role and management strategies of students in improving the quality of education. Using a qualitative method based on literature studies, this study collects data from various references such as books, journals, and scientific articles. The main source of data for this study is scientific articles published in various journals and indexed on the Google Scholar database. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that effective student management involves various aspects, including transparent new student admissions, appropriate student grouping, potential development through structured programs, handling student problems, and integrated data and administration management. Good management has a positive impact on learning motivation, student engagement, character formation, and discipline. However, challenges such as limited resources, lack of teacher training, diversity of student characters, and low communication with parents are still obstacles. To overcome this, it is necessary to strengthen the management system, teacher training, use of technology, and collaboration with parents. With effective management, students not only achieve optimal academic results but also develop in terms of character and social skills, supporting the achievement of holistic educational goals.